Pelatihan Pembuatan Prakarya Edukatif bagi Guru sebagai Upaya Meningkatkan Kreativitas Anak Usia Dini - Dessy Syofiyanti; Dian Purnomo; Yolla Franssisca (SIGMA : Jurnal Sinergi Mengabdi, 2025)
Creativity is one of the important aspects of early childhood development that needs to be stimulated from an early age through a fun and contextual approach. One of the effective media to develop children's creativity is educational crafts, because they are able to train fine motor skills, imagination, and divergent thinking skills. However, there are still many PAUD teachers who do not have adequate skills and knowledge in designing and making crafts that are in accordance with the stage of child development. In response to this, this community service activity aims to improve teachers' competence in making educational crafts with the Asset Based Community Development (ABCD) approach, which focuses on utilizing the potential and assets owned by the community. The activity was carried out in District Rengat involving 25 teachers from various PAUD institutions. The implementation stages include mapping local assets, training on techniques for making crafts from recycled and local materials, and implementation assistance in learning. The results showed that teachers were able to create various types of thematic crafts that were interesting and supported learning, such as story dolls made of patchwork, letters and numbers from cardboard, and environment-based props. In addition to improving teachers' skills, another impact observed is the increase in children's participation and enthusiasm in learning activities. This training not only builds teacher capacity, but also encourages community collaboration in supporting children's creativity. This service is expected to be a sustainable first step in improving the quality of early childhood education services based on local potential.